Two-Dose Severe Acute Respiratory Syndrome Coronavirus 2 Vaccine Effectiveness With Mixed Schedules and Extended Dosing Intervals: Test-Negative Design Studies From British Columbia and Quebec, Canada. (19th April 2022) - Skowronski, Danuta M; Febriani, Yossi; Ouakki, Manale; Setayeshgar, Solmaz; El Adam, Shiraz; Zou, Macy; Talbot, Denis; Prystajecky, Natalie; Tyson, John R; Gilca, Rodica; Brousseau, Nicholas; Deceuninck, Geneviève; et al.
Abstract: Background: The Canadian coronavirus disease 2019 (COVID-19) immunization strategy deferred second doses and allowed mixed schedules. We compared 2-dose vaccine effectiveness (VE) by vaccine type (mRNA and/or ChAdOx1), interval between doses, and time since second dose in 2 of Canada's larger provinces. Methods: Two-dose VE against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or hospitalization among adults ≥18 years, including due to Alpha, Gamma, and Delta variants of concern (VOCs), was assessed ≥14 days postvaccination by test-negative design studies separately conducted in British Columbia and Quebec, Canada, between 30 May and 27 November (epi-weeks 22–47) 2021. Results: In both provinces, all homologous or heterologous mRNA and/or ChAdOx1 2-dose schedules were associated with ≥90% reduction in SARS-CoV-2 hospitalization risk for ≥7 months. With slight decline from a peak of >90%, VE against infection was ≥80% for ≥6 months following homologous mRNA vaccination, lower by ∼10% when both doses were ChAdOx1 but comparably high following heterologous ChAdOx1 + mRNA receipt. Findings were similar by age group, sex, and VOC. VE was significantly higher with longer 7–8-week versus manufacturer-specified 3–4-week intervals between mRNA doses. Conclusions: Two doses of any mRNA and/or ChAdOx1 combination gave substantial and sustained protection against SARS-CoV-2 hospitalization, spanning Delta-dominant circulation. ChAdOx1 VE against infection was improved by heterologous mRNA series completion. A 7–8-week interval between first and second doses improved mRNA VE and may be the optimal schedule outside periods of intense epidemic surge. Findings support interchangeability and extended intervals between SARS-CoV-2 vaccine doses, with potential global implications for low-coverage areas and, going forward, for children. Abstract : Test-negative design studies conducted among adults in British Columbia and Quebec, Canada, show two doses of homologous or heterologous SARS-CoV-2 vaccines provide substantial and sustained protection against hospitalization, and reinforce the use of mixed schedules and longer intervals between doses.